Fishbowl Technique towards the Students’ Speaking Skill - Anakotta, Raisa; Nursalim, Nursalim; Latuheru, Reka Judahida (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2020)
The objective of this research is to describe whether or not fishbowl technique can improve students’ speaking of tenth grade of IPS 1 in SMA N 2 Sorong Regency. In this study, the researcher conducted the quantitative research using the method pre-experimental design type of the one group pre-test. Therefore, the researcher took 30 students as the sample from the population. The researcher used SPSS Analysis Version 20.0, the researcher gave the interpretation towards “t” score by comparing t-value with t-table. The researcher interpretation that t-value is 3.048 with the significance value is 0.05. The score of t-table is 2.045 with the significance level of 0.05 with df 29. P-value is 0.0005 < 0.05, it is known that t-value > t-table ( 3.048 > 2.045 ). Meanwhile, the alternative (H1) is accepted and null hypothesis (Ho) is rejected. It means that using fishbowl technique can improve students speaking skill at the tenth of SMAN 2 Sorong Regency. But this technique is not effective towards students’ speaking skill, because it is not achieve score of KKM that is > 68.